The Formation of β, 1 → 4 Glucan from UDP-α-d-Glucose Catalyzed by a Phaseolus aureus Enzyme - Clark, A. F. (1972)
Particulate enzyme preparations from Phaseolus aureus hypocotyls catalyze the formation of an alkali insoluble β, 1 → 4 linked [(14)C]-glucan using UDP-α-d [(14)C]-glucose as substrate. Particulate enzymes prepared from root tissue also catalyzed the production of β, 1 → 4 glucan. UDP-β-d-[(14)C]-glucose would not serve as a substrate for these enzymes. The presence or absence of β, 1 → 4 glucan synthetase activity was independent of tissue source, substrate concentration, or homogenization method. The particulate enzyme also catalyzes the formation of a β, 1 → 3 linked glucan from UDP-d glucose which is usually soluble in hot alkali. The solubility of the β, 1 → 3[(14)C]-glucan decreased when the enzyme was obtained from hypocotyls germinated at a higher temperature. The water-soluble material resulting from the catalyzed reaction includes a large proportion of what appears to be [(14)C]-laminaribiose, and smaller proportions of [(14)C]-laminaritriose and [(14)C]-glucose. There is no detectable quantity of [(14)C]-cellobiose or [(14)C]-cellotriose in the water-soluble material.